NEEDS AND OPPORTUNITIES OF ADEQUATE INTERPRETATION OF THE HAGUE CONVENTION ON THE CIVIL ASPECTS OF INTERNATIONAL CHILD ABDUCTION IN ТHE CASE OF DOMESTIC VIOLENCE - Samardžić, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
At the time when the Hague Convention on the Civil Aspects of International Child Abduction was passed, that was a very logical step and a goal that this Conventionis set before it, and that is prompt return of children wrongfully removed or retained children, was a necessary consequence of the circumstances of that time. Namely, in most cases, men, that is fathers, were those, who illegally took or kept the children. More than thirty years later, the situation in that field has changed in the sense that mothers are now abductors in most cases, mostly seeing that this is the only way to escape from the violence they, or their children, are facing with. In that sense, the question is whether the achievement of the objective of this Convention is still justified, that is would it be justified any other interpretation of the Convention in situations where the unlawful removal or retention of children is a result of domestic violence.